Assessment Of Cataract Morphology And Visual Outcomes After Surgery Nuclear, Cortical, Posterior Subcapsular Cataract. - Khan, Jehanzeb; Rafiq, Muhammad; Zeeshan Tahir, Muhammad; Waseem , Muhammad; Hamza, Syed Amir (Journal of Neonatal Surgery, 2025)
Background: Cataract remains a leading cause of preventable blindness worldwide. With respect to visual acuity, the complexity, the surgery, and the postoperative outcomes, the various forms of cataracts, i.e., nuclear, cortical, and posterior subcapsular, may cause variations. It is essential to address differences in postoperative recovery for each type of cataract extraction. This would aid in selecting the right patients, providing appropriate pre-surgery counseling, and managing reasonable expectations during postoperative recovery in a low-resource environment. Objectives: To identify the various cataract morphologies and to evaluate differences in visual outcomes before and after cataract extraction with intraocular lens implantation. Methodology: A cross-sectional study was conducted on 120 patients aged 40 years who underwent cataract extraction. The type of cataract was classified using slit lamp biomicroscopy. Visual acuity was measured with a Snellen chart before and after the surgery. All patients had phacoemulsification or extracapsular extractions and had a posterior chamber intraocular lens implanted. The data were analyzed using SPSS v24.0, and paired t-tests and ANOVA were used to assess vision improvement across groups. A p-value < 0.05 was statistically significant. Patients with retinal disease, glaucoma, a corneal opacity, or those who had had previous intraocular surgery were excluded. Results: 120 patients (mean age 63.4 ± 8.2 years), nuclear cataract was most common (45%), followed by cortical (32%) and posterior subcapsular cataract (23%). PSC patients had the poorest preoperative visual acuity, with 78% below 6/60. Postoperatively, all groups showed significant improvement (p <0.001). PSC patients demonstrated the greatest gain, with 82% achieving ≥6/12 vision at six weeks. Nuclear and cortical cataracts achieved ≥6/12 in 76% and 70% of cases, respectively. ANOVA confirmed a statistically significant difference in mean improvement across morphologies (p = 0.03). Minor postoperative edema occurred in 8% and resolved conservatively. Conclusion: The morphology of the cataracts affects how much baseline functionality is lost and how much functionality is regained after surgery, and PSC cataracts show the most significant improvement after surgery. PSC cataracts affect vision more than other types; therefore, cataract surgeries are more effective for PSC cataracts.